USA mot Al-Arian - Halvorsen, Line (Norway : Dalchows Verden, 2007)
A close portrait of an Arab-American family facing terrorism charges leveled by the U.S. Government. The film shows the story of a family living in a society where fear of terrorism has resulted in increasing stigmatization and discrimination against Muslims.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films